2017
DOI: 10.5530/ijper.51.3s.45
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Phytochemical Contains, Antioxidant and Antimicrobial Activities of Malus floribunda Siebold ex Van Houtte From Eastern Turkey

Abstract: Objective: M. floribunda is an ornamental and landscape plant in Turkey and it's small fruits are consumed as food. Antimicrobial, antioxidant activities and phytochemical contents of M. floribunda were investigated. Material and Method: M. floribunda was collected from different localities in the province of Elazig-Turkey. The nutritive value (flavonoid, sugar, fatty acid, vitamin, protein, element), antioxidant (lipid peroxidation, glutathione amounts and DPPH) and antimicrobial activities (on thirteen bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Köpük kurutma yöntemiyle kurutulan toz ürünün, tüm kurutma koşullarında kırmızılık ve parlaklık değerleri, kontrol ve MD ilaveli örneklerden daha yüksektir (P <0.05), ancak antosiyanin içeriğinin kuruma sıcaklığı artışına bağlı olarak azaldığı görülmüştür. Anahtar kelimeler: Malus floribunda, köpük, bakla proteini, toz ürün özellikleri Evaluation of foam-mat drying behaviour INTRODUCTION Malus floribunda is an ornamental plant classified in Rosacea family, and the plant is originated from Japan, therefore it is also called as Japanese crab apple tree (Cepeda and Villaran, 1999;Kırbağ and Aydoğan, 2017). Although the plant is cultivated in landscapes for its beautiful pink-reddish flowers, the apples with sour and astringent taste are used for production of vinegar and marmalade in Turkey as a remedy against diabetes (Kırbağ and Aydoğan, 2017;Coklar et al, 2018).…”
Section: Süs Elmasi (Malus Floribunda) Suyunun Köpük Kuruma Davranişi Ve Toz üRünün Kali̇te öZelli̇kleri̇ni̇n Beli̇rlenmesi̇ öZunclassified
See 2 more Smart Citations
“…Köpük kurutma yöntemiyle kurutulan toz ürünün, tüm kurutma koşullarında kırmızılık ve parlaklık değerleri, kontrol ve MD ilaveli örneklerden daha yüksektir (P <0.05), ancak antosiyanin içeriğinin kuruma sıcaklığı artışına bağlı olarak azaldığı görülmüştür. Anahtar kelimeler: Malus floribunda, köpük, bakla proteini, toz ürün özellikleri Evaluation of foam-mat drying behaviour INTRODUCTION Malus floribunda is an ornamental plant classified in Rosacea family, and the plant is originated from Japan, therefore it is also called as Japanese crab apple tree (Cepeda and Villaran, 1999;Kırbağ and Aydoğan, 2017). Although the plant is cultivated in landscapes for its beautiful pink-reddish flowers, the apples with sour and astringent taste are used for production of vinegar and marmalade in Turkey as a remedy against diabetes (Kırbağ and Aydoğan, 2017;Coklar et al, 2018).…”
Section: Süs Elmasi (Malus Floribunda) Suyunun Köpük Kuruma Davranişi Ve Toz üRünün Kali̇te öZelli̇kleri̇ni̇n Beli̇rlenmesi̇ öZunclassified
“…Anahtar kelimeler: Malus floribunda, köpük, bakla proteini, toz ürün özellikleri Evaluation of foam-mat drying behaviour INTRODUCTION Malus floribunda is an ornamental plant classified in Rosacea family, and the plant is originated from Japan, therefore it is also called as Japanese crab apple tree (Cepeda and Villaran, 1999;Kırbağ and Aydoğan, 2017). Although the plant is cultivated in landscapes for its beautiful pink-reddish flowers, the apples with sour and astringent taste are used for production of vinegar and marmalade in Turkey as a remedy against diabetes (Kırbağ and Aydoğan, 2017;Coklar et al, 2018). Red flesh of this apple reflects richness of anthocyanin pigments; however the literature is limited only about the phytochemical and antimicrobial properties of apple and the rheological properties of concentrated apple juice rather than utilizing the fruit as a food ingredient Kırbağ and Aydoğan, 2017;Coklar et al, 2018).…”
Section: Süs Elmasi (Malus Floribunda) Suyunun Köpük Kuruma Davranişi Ve Toz üRünün Kali̇te öZelli̇kleri̇ni̇n Beli̇rlenmesi̇ öZmentioning
confidence: 99%
See 1 more Smart Citation
“…A study examining the antimicrobial and antioxidant activities and the phytochemical content of M. floribunda has shown that it is rich in phytosterols (ergosterol, stigmasterol, β-sitosterol, and retinol), vitamins (A, D, E, and K), minerals (Cu, Zn, Mn, Fe, Ca, and Mg), protein, unsaturated fatty acids such as linolenic, oleic and palmitic acid, and flavonoids (rutin, morin, quercetin, and naringenin). Moreover, edible M. floribunda fruits have been regarded as important nutritional sources of food compounds and functional benefits (Kırbag & Aydogan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…M. floribunda trees are generally used for pollination in apple nurseries and ornamentation as well as in the production of apple juice and jelly (Altuntas & Karaosman, 2015; Vaughan & Geissler, 1997). In Turkey, M. floribunda is generally used as an ornamental or landscape plant and its fruits are favored by diabetic patients as a blood sugar‐regulating agent (Kırbag & Aydogan, 2017). A study examining the antimicrobial and antioxidant activities and the phytochemical content of M. floribunda has shown that it is rich in phytosterols (ergosterol, stigmasterol, β‐sitosterol, and retinol), vitamins (A, D, E, and K), minerals (Cu, Zn, Mn, Fe, Ca, and Mg), protein, unsaturated fatty acids such as linolenic, oleic and palmitic acid, and flavonoids (rutin, morin, quercetin, and naringenin).…”
Section: Introductionmentioning
confidence: 99%